Picturing the Art of Teaching: A Faculty Development Workshop - Jeff Pettit (Association of American Medical Colleges, 2015)
Abstract For facilitators, training an audience about different teaching techniques can reside on a continuum from straight didactics to open practice. The challenge is to make the training intellectually stimulating and interactive. This workshop format does both. Similar to the board game Pictionary, this workshop requires participants to draw various teaching methods within a set time frame. One participant at a time selects a card from three different areas (clinical, classroom, crossover) and attempts to draw a picture so that other members of his/her group can guess the technique within 75 seconds. Then, the facilitator briefly discusses the technique and asks if anyone has used it. After the debriefing, a new participant artist selects a card. This publication includes the presentation, cards, timer, and evaluation form for successful implementation by other institutions. Information on all of the techniques in this workshop comes from multiple sources and from experiences of the author. This workshop was designed in Fall 2014 as a creative means of introducing different teaching techniques in a fun and interactive way. The game has been presented in three different settings, after which attendees have requested the materials. It was presented to the community teaching scholars at the Carver College of Medicine, University of Iowa, in Fall 2014; to pediatricians at Blank Children's Hospital in Des Moines, Iowa, in Winter 2015; and at the 2015 Teach the Teacher conference at the University of Arkansas for Medical Sciences.